Prospective, Randomized, Multicenter, Controlled Trial (TRIATHRON 1) on a New Antithrombogenic Hydrophilic Dialysis Membrane. Issue 5 (May 2017) - Ronco, Claudio; Brendolan, Alessandra; Nalesso, Federico; Zanella, Monica; De Cal, Massimo; Corradi, Valentina; Virzì, Grazia M.; Ferrari, Fiorenza; Garzotto, Francesco; Lorenzin, Anna; Karopadi, Aakash N.; Sartori, Marco; et al.
Introduction: Hemodialysis treatment requires anticoagulation to prevent thrombosis of the dialyzer. The Hydrolink ® (NV series; Toray) has been designed to reduce thrombotic complications by increasing membrane hydrophilic properties. Previous studies have confirmed reduced platelet activation, improved removal of β2-microglobulin and excellent small-solute removal. Methods: We designed a prospective, multi-centered, randomized clinical study to compare the antithrombogenic effects (platelet count) of NV dialyzers versus conventional treatment. To compare the possibility of performing heparin-free dialysis, we carried out progressive heparin reduction tests. Patients with an average platelet count lower than 170, 000 cells/mm 3 using standard high flux membranes in the 6 months prior to the study were enrolled and randomized. Patients were either dialyzed for 6 months without changing the previous membrane (control group) or treated with the Hydrolink ® membrane (NV group). After the third week, the heparin reduction test was conducted for 5 weeks in order to assess the minimum amount of anticoagulant needed to safely perform a 4-hour dialysis treatment. Performance and safety were evaluated measuring platelet count and activation, middle-molecule removal rate and nutritional status. Results: We found no significant difference in platelet count, platelet activation factors β-thromboglobulin and platelet factor 4 (PF-4), between the groups. More patients in the study group reached heparin-free dialysis without clotting events during the heparin reduction test. The NV dialyzers displayed anti-thrombogenic effects as compared to conventional dialyzers. Conclusions: The NV dialyzer series is safe with no adverse events reported. Further studies are required to understand the mechanisms of anti-thrombogenic effects.